Kyrgyz Republic : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2008)
This report provides a reassessment of fiscal transparency practices in the Kyrgyz Republic against the requirements of the IMF Code of Good Practices on Fiscal Transparency. It gives a description of practice on the basis of discussions with the authorities and their responses to the fiscal transparency questionnaire. It also provides the details of a staff report on fiscal transparency in the Kyrgyz Republic, and includes an assessment of practices against the Guide on Resource Revenue Transparency.